Kesiapsiagaan Siswa dalam Menghadapi Bencana Gempa Bumi dan Tsunami - Ela Nurdiawati; Ahmad Jubaedi; Rofika Ainin Holila (Universitas Faletehan, 2024)
Indonesia was ranked second out of the 10 most earthquake-prone countries in the world. The impact of the earthquake was not only felt by the general public, but also affects learning activities in schools from elementary to high school levels. The purpose of this study was to determine students' preparedness in facing earthquake and tsunami disasters. The samples of this study consisted of 143 respondents who were students in grades VII, VIII and IX at Madrasah Tsanawiyah Negeri 3. Determining the number of samples in each class used purposive sampling with the type of observational research. The collected data was analyzed descriptively using frequency tabulation. The preparedness was measured based on four indicators, namely level of knowledge, emergency response plan, early warning system and resource mobilization. The findings showed that the level of preparedness and level of knowledge of students was in the medium category. Emergency response plans, early warning systems and resource mobilization were in the high category. The level of students' knowledge of disaster preparedness must be increased, especially in terms of knowledge of the differences in emergency response sirens. The findings in the field indicated the need to update the evacuation route map and put-up preparedness posters in each class. Mobile phones can be utilized as a medium of education and promotion regarding earthquake and tsunami disasters and evacuation mechanisms for natural disasters.